Whole-genome sequencing of endophytic Bacillus cereus ELSZ6 isolated from Smilax zeylanica L. reveals antimicrobial potential against multidrug-resistant pathogens - Zuhri, Rozana; Retnaningrum, Endah; Widiyastuti, Yuli; Susidarti, Ratna Asmah (Indonesian Journal of Biotechnology, 2026)
The increasing global prevalence of multidrug-resistant (MDR) bacterial infections has intensified the search for new antibacterial agents from underexplored natural sources. Endophytic bacteria associated with medicinal plants are recognized as potential producers of bioactive secondary metabolites. This study aims to isolate and characterize antibacterial endophytic bacteria from Smilax zeylanica collected in Bukit Duabelas National Park, Jambi, Indonesia. Endophytic bacteria were isolated from roots, stems, leaves and rhizomes using a surface sterilization method, which was validated by a final rinse test which showed no microbial growth. Antibacterial activity was screened using a dual culture assay on Nutrient Agar against methicillin-resistant Staphylococcus aureus (MRSA) WS 29 and Escherichia coli RES 22-2020, followed by phenotypic and genomic characterization. A total of 45 endophytic bacterial strains were obtained, of which seven exhibited inhibitory activity against both pathogens. Strain ELSZ6 showed the strongest inhibition and was characterized as Gram-positive, rod-shaped, and endospore-forming. Whole genome sequencing identified the strain as Bacillus cereus (6.3 Mbp; 50× coverage). Genome mining using antiSMASH revealed several biosynthetic gene clusters associated with secondary metabolites, including bacillibactin, zwittermicin A and petrobactin. The findings indicate that strain ELSZ6 represents a potential candidate for further investigation as a source of antibacterial compounds for use against MDR bacteria.